The role of the Environmental Education in tackling the Climate Emergency and biodiversity decline: articulating Brazilian experiences - Louro Ferreira Silva, Rosana; Grandisoli, Edson; Jacobi, Pedro Roberto (International Journal of Environmental Resilience Research and Science, 2024)
Abstract: The transition to more sustainable societies is permeated by interests, conflicts, and predatory use of natural resources, generating vulnerability, socio-environmental injustice, and poverty. Considering that we are living in an era of uncertainty and multiplication of complex and wicked issues due to the prevailing logic of society, there is an urgent and unquestionable need to re-think educational paradigms, considering the need to redesign actions within transitional and transformational perspectives. This work describes and analyzes two educational experiences related to central and connected socio-environmental challenges: biodiversity loss and climate emergency. Both experiences encompass ways created to empower teachers to understand the complexity and create paths for action, highlighting the crucial role of participation and cooperation among different social institutions such as Governmental, Universities and NGOs. The challenge is to build communities as territory transformative agents in the use of active learning methodologies that promote meaningful knowledge from a perspective of the global South. Key Words: Social learning. Sustainable societies. Climate schools. Teacher training.